EFFECTS OF SOYBEAN JUICE (Glycine max L.) ON SPERMATOZOA FERTILITY AND TESTICULAR WEIGHT IN RATS (Rattus norvegicus L.) - Wa Ode Harlis; Isdayanti Isdayanti; Nurhayu Malik; Takdir Saili; Resman Resman (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Soybeans (Glycine max L.) contain isoflavone compounds which can disrupt hormonal balance through negative feedback on the hypothalamic-pituitary-gonadal axis causing inhibition of Leydig cell activity and Sertoli cell function. The aim of this research was to determine the effect of giving soybean juice on spermatozoa fertility and testicular weight in rats (Rattus norvegicus L.). This type of experimental research was structured based on a Completely Randomized Design (CRD) pattern consisting of 4 treatments and 6 replications, namely K (control/drinking water), P1 (7.1 g/kgBW/day), P2 (14.2 g/kgBW/day) and P3 (21.3 g/kgBW/day). Soybean extract was given for 49 days, and on the 50th day the rats were sacrificed and dissected to observe variables in the form of testicular weight and spermatozoa fertility (morphology, pH and viscosity). Data were analyzed using ANOVA and further BNT test α=0.05. The results showed that administration of soybean extract caused a decrease in the percentage of testicular weight and spermatozoa fertility. Testicular weight is K=0.98 g. P1=1.08 g, P2=0.77g and P3=0.62 g. The percentage of abnormal spermatozoa morphology increased, namely K = 17.8%, P1 = 37.0%, P2 = 47.7%, P3 = 56.0%. The acidity of sperm pH increases, namely K= 7.50, P1=6.17, P2=5.67, and P3=5.83. Sperm-matozoa viscosity decreased, namely K=1.57, P1=1.58, P2= 0.76 and P3=0.77. The results of the study concluded that soybean juice caused a decrease in testicular weight and spermatozoa fertility in mice.